Abandoned mine slags analysis by EPMA WDS x-ray mapping - Guimarães, Fernanda (2010)
The mining activity on the Iberian pyritic Belt (Portugal and Spain) started before Phoenician times, became particularly intense during the Roman occupation of the Iberian Peninsula (for gold) and after the industrial revolution (for gold, copper, zinc, lead and sulphur). The commonest ore of this region is a massive polymetalic sulphide accumulation, where pyrite (FeS2) is the main mineral, with variable concentrations of chalcopyrite (CuFeS2), sphalerite (ZnS), galena (PbS), arsenopyrite (FeAsS2), other sulphides and sulfosalts which include minor elements like Mn, Co, Ni, Se, Cd, Sb, Te, Hg and Bi. Some of the main and minor elements of these ores are hazardous and the drainage basins of pollutant source areas often induce health concerns in the resident population. Electron microprobe study followed previous optical and XRD analysis of the slags. The study focused on the identification of phases how sulphide and meta11ic phases are distributed within the material and infer about leachable elements during weathering. Electron microprobe X-Ray maps show evidences of different behavior between the elements: Ca and Zn are completely leached; iron is retained in oxyhydroxides, lead and arsenic precipitate as sulphates. Electron microprobe studies are essential to understand complex materials as earth materials. Nevertheless, care is required to a correct interpretation of data and most quantitative compositional data are not trustworthy.